Una olimpiada matemática para el segundo ciclo (OMCEP) (ING) - Buján, Víctor (2003)
We describe the origin, development and objectives of the Mathematical Olympiads “OMCEP”, an annual contest for Grades 4, 5 and 6 that took place for the first time in 1993. Lists of medal winners for the last three years of OMCEP, and some problems, with the percentages of correct answers given by participating children, are shown.